2021
DOI: 10.1002/aelm.202100166
|View full text |Cite
|
Sign up to set email alerts
|

Processable Thiophene‐Based Polymers with Tailored Electronic Properties and their Application in Solid‐State Electrochromic Devices Using Nanoparticle Films

Abstract: The development of semiconductor polymers for electronic applications requires tailored synthetic strategies to obtain materials with tunable electronic properties and morphology to enhance their properties. Towards this goal, here is reported the expedient synthesis of a novel class of thiophene‐based electrochromic polymers, processable in organic solvents and as nanoparticles (NPs) in water. Their characterization and application in flexible solid‐state electrochromic devices (ECDs) are described. All polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Polythiophenes, one of the most important classes of conjugated polymers, have been extensively investigated for their great optical properties [ 16 , 17 , 18 , 19 ]. Indeed, polythiophene and its derivatives are typically characterized by a relatively stable conductivity level and optical transparency, which are relevant for various applications [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polythiophenes, one of the most important classes of conjugated polymers, have been extensively investigated for their great optical properties [ 16 , 17 , 18 , 19 ]. Indeed, polythiophene and its derivatives are typically characterized by a relatively stable conductivity level and optical transparency, which are relevant for various applications [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is in correlation with the increasing use of similar molecules in organic bioelectronic devices. Previous work has shown that the electrical properties of thiophenes can be tuned by introducing alkoxy substituents 63,64 . Their enrichment among the chemically synthesizable radicals may also be due to the availability of reaction templates for this chemistry, as only 104 of the 232 DFT-confirmed RL candidates possess this functional group.…”
Section: Development Of a Fast Surrogate Multi-objective Functionmentioning
confidence: 99%
“…Thiophene-based conjugated polymers have made remarkable progress, which is attributed to their unique semiconducting properties and effective charge carrier transport properties. 60,95,96 Polythiophene was first discovered to be a highly conductive polymeric material but had poor solubility. However, poly(3-hexylthiophene) (P3HT) has attracted considerable attention due to the introduction of hexyl side chains to improve its solution processability.…”
Section: Semiconducting Polymers Based On Diarylethylene Unitsmentioning
confidence: 99%